Energy harvesting via piezoceramics in unmanned aerial vehicles - Ng, Nicholas Jun Hao (2015)
This study investigates the feasibility of vibrational energy harvesting through extracting aircraft vibrations with the aid of piezoceramic materials within the wing section of a selfdesigned and 3D-printed unmanned aerial vehicle (UAV). The piezoceramic materials are placed at different locations of the UAV wing to harvest the possible maximum average voltage output. Although the self-designed prototype is of an inconventional model, the purpose was to replicate the existing militaries UAVs being operated at present. Vibrational energy harvesting is an enticing technology for small-scale UAVs as it offers the potential to boost flight endurance without significant mass addition or expansion of fuel systems. Experimentation was carried out on the UAV prototype with a wing span of 0.54 metres in a wind tunnel facility to simulate the real-time flight condition at 20 m/s using two different sized piezoceramic materials respectively. To further enhance the experiments, modifications were made where installation of magnet strips were located at the top and bottom of the wing section. The magnet strips was found to excite further vibrations on the V22BL piezoceramic energy harvester with the use of a magnetic proof mass at a maximum average voltage output of 613 mV. These real time experiments show the potential of such an energy harvesting implementation in UAVs for having the providence of local energy sources for wireless sensors. However, increasing the flight endurance of the prototype based on this implementation has not been proven feasible due to the inconsistency in the vibrations on the wings and the tradeoffs of additional weights of the piezoceramics on the prototype.